2017
DOI: 10.1175/jtech-d-16-0192.1
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Current Measurements in the Northern North Sea

Abstract: A met-ocean measurement program of waves and current profiles at five locations in the northern North Sea was performed over a period of approximately 5 years. Despite quality control, the measured current speed data contained more noise than expected and large discrepancies were observed between overlapping current speed data measured by different current profilers at the same locations and water depths. Some of the noise and discrepancies can be explained by the influence from surface waves. The current meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Inertial oscillations with smaller Cs are also observed. These wind-generated inertial oscillations resulting in large Cs August 2014 with Cs around 60 cm/s and 80 cm/s, respectively, Bruserud and Haver (2017a) found that the current conditions at Location 1 differ from the three other locations. As Location 1 is located further north in the northern North Sea in an area with steeper bottom topography and larger water depths, than the other 3 locations, other phenomena than wind-generated inertial oscillations such as large-scale current contribute to the current conditions here.…”
Section: Inertial Oscillationsmentioning
confidence: 93%
See 4 more Smart Citations
“…Inertial oscillations with smaller Cs are also observed. These wind-generated inertial oscillations resulting in large Cs August 2014 with Cs around 60 cm/s and 80 cm/s, respectively, Bruserud and Haver (2017a) found that the current conditions at Location 1 differ from the three other locations. As Location 1 is located further north in the northern North Sea in an area with steeper bottom topography and larger water depths, than the other 3 locations, other phenomena than wind-generated inertial oscillations such as large-scale current contribute to the current conditions here.…”
Section: Inertial Oscillationsmentioning
confidence: 93%
“…The measured current data showed that currents from wind-generated inertial oscillations dominate the current conditions in the northern North Sea and also generate the largest observed current speeds (Bruserud and Haver 2017a). Following this, a simple mathematical model for wind-generated inertial oscillations can be applied to simulate current conditions of a longer duration for the northern North Sea.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations